Fibre-type-specific and mitochondrial biomarkers of muscle damage after mountain races - Carmona, G.; Roca, E.; Guerrero, M.; Cussó, R.; Bàrcena, C.; Mateu, M.; Cadefau, J. A. (International Journal of Sports Medicine, 2019)
Consequences of running mountain races on muscle damage were investigated by analysing serum muscle enzymes and fibre-type-specific sarcomere proteins. We studied 10 trained amateur and 6 highly trained runners who ran a 35 km and 55 km mountain trail race (MTR), respectively. Levels of creatine kinase (CK), CK-MB isoform (CK-MB), sarcomeric mitochondrial CK (sMtCK), transaminases (AST and ALT), cardiac troponin I (cTnI) and fast (FM) and slow myosin (SM) isoforms, were assessed before, 1 h, 24 h and 48 h after the beginning of MTR. Significant SM increases were found at 24 h in the 55 km group. Levels of CK, CK-MB, AST and cTnI were significantly elevated in both groups following MTR, but in the 55 km group they tended to stabilize in at 48 h. Using pooled data, time-independent serum peaks of SM and CK-MB were significantly correlated. Moreover, concentration of sMtCK was significantly elevated at 1 and 24 h after the race in the 35 km group. Although training volume could confer protection on the mitochondria, the increase in serum CK-MB and SM in the 55 km group might be related to damage to the contractile apparatus type I fibres. Competing in long-distance MTRs might be related to deeper type I muscle fibre damage, even in highly trained individuals